Local analysis, global thinking: structure and dynamics of collaborative relations in science education research - Fontes, Daniel Trugillo Martins (2024)
This article is grounded in the structural perspective of social networks to explicitly address gaps in Science Education research. First, it assesses the structure and evolution of the coauthorship network in Science Education research within non-formal education over 40 years of investigation. The analysis underscores the fragmentation and the emergence of a small-world model, with researchers forming locally connected clusters through the establishment of new coauthorship ties, as well as researchers crossing boundaries. The implications of these findings for research activities are discussed. The discussion is then extended to other specialties in the field of Science Education research, suggesting that engaging in multiple specialties serves as an organizing axis for collaboration relationships resulting in coauthorship. Empirically, it is observed that works with two or three authors and high fragmentation indices constitute the norm in specialty areas of the Science Education research field. Furthermore, there are indications that the specialty area in Science Education research does not necessarily make it more collaborative. Finally, limitations are discussed, and suggestions for future research directions are proposed. In conclusion, overcoming methodological challenges in constructing a consolidated database is identified as another crucial step in advancing the maturity of the Science Education research field.